COMPLIANCE TO DRUG USE IN HYPERTENSIVE PATIENTS AND ITS RELATIONSHIP WITH VARIABLES AFFECTING IN THREE CITIES IN INDONESIA - MUHLIS, MUHAMMAD; KARLINA, DEWI; NAMITA, MERLI; MARESTA, LALA; FEROLIA, YOCIKA ESTI (International Journal of Applied Pharmaceutics, 2021)
Objective: Patient noncompliance in taking medication is the problem in hypertension therapy. This study aims to describe the compliance to drug use in hypertensive patients in Bengkulu, Banjarmasin, and Yogyakarta, Indonesia. Methods: This study is an observational study using a questionnaire, with a total sample size of 300. Data are analyzed by using bivariate analysis with the chi-square method to see if there is a relationship between compliance and predetermined variables. Results: The study in three cities showed that there were 0 patients (0%) Low compliance and non-compliance category patients; the compliance category was 91%, 10%, 8%, respectively. High compliance categories were 9%, 90%, 92%. Chi-square test shows that compliance has a significant relationship (*P<0.05) in the three cities on the variable "treatment motivation", other variables that show a significant relationship in the city of Yogyakarta are "drug side effects", "role of health workers", "social support", in Bengkulu is "Therapeutic beliefs", in Banjarmasin is" Knowledge of therapeutic effects ". Conclusion: All hypertensive patients have good compliance; compliance is significantly associated in all three cities on the variable "treatment motivation."